Cover Image. (14th September 2018) - Chen, Z.; Peng, Y.; Ng, C.L.; Jin, P.; Liu, J.; Li, Y.Y.; Yan, Y.; Liu, Y.H.; Luo, X.L.; Qiu, Q.H.; Wang, D.Y.
Abstract : The cover image, by Zhuo Chen et al., is based on the Correspondence The clinical characteristics and histopathological features of chronic rhinosinusitis with unilateral nasal polyps in 136 patients in Southern China, DOI:10.1111/coa.13147 .